2005
DOI: 10.1063/1.2112184
|View full text |Cite
|
Sign up to set email alerts
|

Application of carbon nanotube field emission effect to an ionization gauge

Abstract: Using the field emission effect of a carbon nanotube (CNT), we characterized a new type of technology for detecting low pressure. The fabricated low pressure sensor is of a triode type, consisting of a cathode (carbon nanotubes field emitter arrays), a grid, and a collector. The gauge described here has a triode configuration similar to that of a conventional hot cathode ionization gauge but also has a cold emission source. Due to the excellent field emission characteristics of CNT, it is possible to make a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Electron field emission from sharp emitter tips, such as carbon nanotubes, becomes more and more important when D ≤ L. There are possible applications using field emission of electrons in nanoelectromechanical systems 7 or in the development of low energy consumption lamps, 15,16 ion gauges, 17,18 X-ray sources 19 and flat panel displays. 20 It is therefore very important to have a quantitative description of how the field enhancement factor is affected when the separation between the emitter tip and the anode is changed, since this will affect the tunneling current.…”
Section: Electric Field Enhancement Factors Around a Metallic End-camentioning
confidence: 99%
“…Electron field emission from sharp emitter tips, such as carbon nanotubes, becomes more and more important when D ≤ L. There are possible applications using field emission of electrons in nanoelectromechanical systems 7 or in the development of low energy consumption lamps, 15,16 ion gauges, 17,18 X-ray sources 19 and flat panel displays. 20 It is therefore very important to have a quantitative description of how the field enhancement factor is affected when the separation between the emitter tip and the anode is changed, since this will affect the tunneling current.…”
Section: Electric Field Enhancement Factors Around a Metallic End-camentioning
confidence: 99%
“…Kornienko et al 4 evaluated a cold cathode electronimpact ion source made from an array of diamond-coated silicon whiskers for application in an ion trap mass spectrometer. Others have reported traditional vacuum ion gauges utilizing carbon nanotubes 5,6 ͑CNTs͒ and molybdenum tips 7 as the electron source. Chalamala et al 8 reported on the realtime pressure measurement inside field emission displays using integrated field emitters for electron-impact ionization.…”
mentioning
confidence: 99%
“…The emission current between a diamond cathode and an anode changes with a change in the vacuum gap caused by a deflection of a diaphragm under external gas pressures in diaphragm-type pressure sensors. [9][10][11][12] Recently, carbon nanotubes (CNTs) have been adopted as electron emitters and have sensed gas at low pressure (<133 Pa) 13,14 and at atmospheric pressure, 15 exploiting gas ionization and discharge. Gas discharge devices have also been adopted to protect electrical circuits from power surge and electrostatic discharge.…”
Section: Introductionmentioning
confidence: 99%